Analisis Kemampuan Berpikir Kritis dan Sikap Peduli Lingkungan Peserta Didik SMP Kelas VII pada Materi Pemanasan Global di SMP Negeri 29 Medan - Gracia Hillary; Ely Djulia; Ridha Harni Hasibuan (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the critical thinking skills of seventh grade junior high school students on global warming material at SMP Negeri 29 Medan in the 2021/2022 Academic Year, and the attitude of caring for the environment towards global warming material. This type of research is descriptive with mixed research methods. The population in the study consisted of 8 classes and the sample consisted of 2 classes, namely class VII-7 and VII-8 with 62 students. The sampling technique used is random sampling. The research data collection used a HOTS-based essay test instrument totaling 12 items, an interview instrument totaling 7 questions, an environmental care attitude questionnaire totaling 15 statements, and also observation sheets of learning tools. The results showed that students' critical thinking skills could be categorized as low with an average percentage score of 47.50. Factors that influence students' critical thinking skills are situational factors and dispositional factors. The most influential situational factor is the accountable factor, while the most influential dispositional factor is habituation and practice. The caring attitude of students in class VII at SMP Negeri 29 Medan for the 2021/2022 school year can be categorized as not caring with an average percentage score of 49.78.